2015
DOI: 10.1159/000438573
|View full text |Cite
|
Sign up to set email alerts
|

Role of Hyperketonemia in Inducing Oxidative Stress and Cellular Damage in Cultured Hepatocytes and Type 1 Diabetic Rat Liver

Abstract: Background/Aims: Type 1 diabetic (T1D) patients have a higher incidence of liver disease. T1D patients frequently experience elevated plasma ketone levels along with hyperglycemia. However, no study has examined whether hyperketonemia per se has any role in excess liver damage in T1D. This study investigates the hypothesis that hyperketonemia can induce oxidative stress and cellular dysfunction. Methods: STZ treated diabetic rats, FL83B hepatocytes, and GCLC knocked down (GSH deficient) hepatocytes were used. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 50 publications
0
17
0
1
Order By: Relevance
“…The present study demonstrated that impeded autophagy and excessive autophagy account (at least in part) for obesity-induced hypertension and endothelial dysfunction. Taken together, obesity-related increased BP and endothelial dysfunction might be corrected (at least in part) by improved autophagic flux via alleviation of oxidative stress [34, 35]. …”
Section: Discussionmentioning
confidence: 99%
“…The present study demonstrated that impeded autophagy and excessive autophagy account (at least in part) for obesity-induced hypertension and endothelial dysfunction. Taken together, obesity-related increased BP and endothelial dysfunction might be corrected (at least in part) by improved autophagic flux via alleviation of oxidative stress [34, 35]. …”
Section: Discussionmentioning
confidence: 99%
“…On human renal fibroblasts, ICAM-1 increased after activation by cross-linking the synthesis of RANTES and IL-8 [ 59 ], the latter acting as a chemo-attractant for granulocytes and is also abundant after differentiation of hbm- and hsubMSC as shown here. Moreover, on liver cells, ICAM-1 allows macrophages recruited by MCP-1 to adhere via the LFA-1 ligand [ 60 ]. This might also substantiate that the MSC differentiated into the hepatocytic lineage, which is also corroborated by the decrease of CD166 expressed as mesenchymal stem cell marker on liver fibroblasts [ 61 ].…”
Section: Discussionmentioning
confidence: 99%
“…ROS play an important role in the development of insulin resistance in the type II diabetes (T2DM) and decrease in the pancreatic β cell functions shown in Fig. 3 [160, 161]. Studies showed that high glucose activates various enzyme in mitochondrial, including NADPH oxidase, NO synthases and xanthine oxidase [162-164].…”
Section: Ros and Diseasesmentioning
confidence: 99%